Targeting PKCθ in alloreactivity and graft-versus-host-disease: unanswered questions and therapeutic potential - Bronk, Crystina; Yu, Xue-Zhong; Beg, Amer (Frontiers in Immunology, 2012)
Protein kinase C isoform θ (PKCθ) is a key modulator of TCR signaling and mediates activation of NF-κB, NF-AT, and AP-1 transcription factors. Although in vitro studies of PKCθ-/- T cells have shown impaired activation responses, in vivo studies indicate that PKCθ requirement is not universal. While PKCθ is important in induction of experimentally induced autoimmune diseases in mice and generation of Th2 responses, it is not essential for induction of T cell proliferative and cytotoxic responses against influenza virus, LCMV, and vaccinia virus. The context-specific involvement of PKCθ in T cell responses suggests that inhibition of PKCθ may be beneficial in some but not all situations. In the bone marrow transplantation (BMT) setting, we have shown that graft-versus-host-disease (GVHD) cannot be induced in the absence of PKCθ. However, graft-versus-leukemia effects and T cell ability to clear virus infection remains intact. Therefore, PKCθ is a potential therapeutic target in BMT, inhibition of which may prevent GVHD while retaining anti-tumor and anti-infection responses.